2021
DOI: 10.4212/cjhp.v74i1.3044
|View full text |Cite
|
Sign up to set email alerts
|

Conflict between Pharmacy Preceptors and Pharmacy Learners in Experiential Education

Abstract: Background: The relationship between a preceptor and a learner is complex and can be prone to conflict. The issue of conflict in experiential education has been studied in medicine, nursing, social work, and education; however, conflict between pharmacy preceptors and learners has not been described. Objective: To describe types of conflict between pharmacy preceptors and learners, the outcomes of such conflict, the impacts on the preceptor-learner relationship, and conflict-resolution strategies. Methods: An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Kendrick and colleagues describe conflict between preceptors and learners, noting that most preceptors (60%) and most learners (75%) reported experiencing conflict with a negative impact on their relationship. 4 The learners in this study also reported feeling that the conflict had a negative impact on their performance at a higher rate than the preceptors, while preceptors were more likely to take steps to seek resolution. The higher rates of perceived conflict and feelings of negative performance impact, along with a lower rate of conflict resolution initiative among learners may stem from the power dynamics between preceptors and learners.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Kendrick and colleagues describe conflict between preceptors and learners, noting that most preceptors (60%) and most learners (75%) reported experiencing conflict with a negative impact on their relationship. 4 The learners in this study also reported feeling that the conflict had a negative impact on their performance at a higher rate than the preceptors, while preceptors were more likely to take steps to seek resolution. The higher rates of perceived conflict and feelings of negative performance impact, along with a lower rate of conflict resolution initiative among learners may stem from the power dynamics between preceptors and learners.…”
Section: Introductionmentioning
confidence: 66%
“…From the student perspective, conflict between the student and preceptor has been documented in relation to unclear expectations, learning style preferences, and communication. 4 Conflicts may naturally arise during experiential education, which may negatively affect working relationships. 4 Students may lack the experience, assertiveness, or psychological safety to resolve disagreements.…”
Section: Student Perception Of Power Dynamicmentioning
confidence: 99%
“…Participants also mentioned the management of challenging or poorly performing students. Conflict management is a wellestablished concern and a recommended area of development for preceptors (Phillips et al, 2014;Kendrick et al, 2021). Staff identified the lack of preceptor training and experience in teaching, with the literature supporting the need for preceptors to be knowledgeable of teaching strategies to motivate and develop students and effectively deliver feedback (O'Sullivan et al, 2015;Williams et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Managing conflict and dealing with unmotivated students, however, was regarded as less important in this study, with correspondingly lower preceptor confidence levels in these areas. Conflict between preceptors and learners was reported to be quite common and lack of confidence of pharmacy preceptors in handling conflict has also been frequently described (Assemi, Corelli, & Ambrose, 2011;Smith et al, 2020;Kendrick et al, 2021). With conflict resolution being regarded as an aspect of professionalism, training in conflict management has been recommended (Kendrick et al, 2021).…”
Section: Discussionmentioning
confidence: 99%